Autumn senescence response to a changing climate: effects of snow-depth on High Arctic plants - Abbandonato, Holly (UiT Norges arktiske universitet, 2014)
Temperature and precipitation in the Arctic are projected to increase over the next century with a changing climate. Understanding how tundra plants respond to this change is still unclear. Little is known about autumn senescence in the Arctic and with a short growing season, timing is critical. If a plant senesces too early, it compromises photosynthetic activity and growth. If a plant senesces too late, it risks losing nutrients to frost damage, limiting next year's growth and reproductive success. This study aims to determine the relationship between the timing of autumn senescence with different snow regimes, in particular, investigating its effects on the day of year, season length, and thawing degree day. Since 2006, snow fences have been used to experimentally manipulate snow-depth in Adventdalen, Svalbard (78°N). Between 2008-2013, the timing of senescence was recorded in eight species: Alopecurus magellanicus, Bistorta vivipara, Cassiope tetragona, Dryas octopetala, Luzula confusa, Pedicularis hirsuta, Salix polaris, and Stellaria longipes spp. longipes subjected to four winter snow treatments (shallow, ambient, medium and deep). The day of snowmelt in the deep (with a snow-depth of ~150 cm) treatment was consistently later than the medium (60-100 cm), ambient (10-35 cm) and shallow (1-5 cm) treatments. In general, later snowmelt resulted in delayed senescence during both senescence start (1-24% of the leaves senesced) and senescence 50 (50-74% of the leaves senesced). All species showed the same treatment effect except for Stellaria longipes ssp. longipes. Delayed snowmelt reduced the season length and the timing of senescence was unrelated to thawing degree days except in the shallow treatment. In conclusion, the timing of senescence was directly influenced by the snow regimes tested, and the consequences of early and delayed senescence may pose challenges to Arctic plants in the next century.